P23 Effect of omalizumab on oral corticosteroid requirements of young children with severe asthma; results of a UK survey. (16th November 2010) - Kirk, A; Spencer, D; Radwan, A
Abstract : Introduction and Objectives: Some children with severe chronic asthma require long-term oral corticosteroids (OCS) to maintain disease control which places them at risk of potentially serious adverse effects. Omalizumab is a recombinant, humanised, monoclonal anti-IgE antibody indicated in the EU for use in patients of ≥6 years of age with inadequately controlled severe allergic asthma. This agent improves disease control in children, adolescents and adults. We conducted an observational survey in UK clinical centres to evaluate whether omalizumab enabled reduction of OCS dose in children with severe, persistent, allergic asthma. Methods: Seven UK clinical centres were identified in which children (6 to <12 years of age) with severe persistent allergic asthma were being treated with omalizumab. Lead clinicians at each centre were approached to request their participation and, if they agreed, they were sent a short questionnaire. Participating clinicians provided information on children who had continued treatment with omalizumab beyond the 16-week responder assessment. Information collected included the number of children receiving omalizumab, OCS use, OCS dose at omalizumab initiation, numbers of children stopping, reducing or increasing OCS use, and current OCS doses. Results: Information was provided from four sites for 18 children receiving omalizumab, all of whom were on maintenance OCS at baseline. All patients were able to stop or reduce their OCS dose after initiating omalizumab. Four patients (22%) on a mean baseline OCS dose of 8.8 mg/day stopped using OCS altogether. In the remaining fourteen patients (78%) the OCS dose was reduced by a mean of 15.4 mg (from 22.0 mg to 6.5 mg; mean 70.2% reduction). The mean dose reduction across all patients of 77% was achieved in a mean time of 14.6 weeks. Conclusions: In this observational survey, all paediatric patients with severe allergic asthma who were commenced on omalizumab were able to stop or reduce OCS use, potentially reducing the risk of OCS-related adverse effects. The reductions in OCS use occurred over a short period, raising the possibility that further reductions in OCS dose might be feasible in some patients over a longer period of time.